Recasting the Iron Rice Bowl: The Reform of China's State-Owned Enterprises - Berkowitz, Daniel; Ma, Hong; Nishioka, Shuichiro (The Review of Economics and Statistics, 2017)
Following the enactment of reforms in the mid-1990s, China's state-owned enterprises (SOEs) became more profitable. Using theoretical insights from Azmat, Manning, and Van Reenen (2012) and Karabarbounis and Neiman (2014) and econometric methods in De Loecker andWarzynski (2012), this paper finds that SOE restructuring was nevertheless limited. This is because SOE profitability gains in part reflect that they were under less political pressure to hire excess labor and also their cost of capital fell and their capital-labor elasticity of substitution generally exceeded unity. Moreover, SOE productivity lagged that of foreign and private firms.